Effect of Bilimbi Fruit Extract (Averrhoa bilimbi L.) on Renal Histological Structure in Mice Induced by Reheated Palm Oil Exposure - Edoryansyah, Purnomo Andimas; ., Muthmainah; Wijayanti, Lilik (Nexus Biomedika, 2016)
Introduction: Oxidative stress has a role in various kidney diseases, such as chronic renal disease, chronic renal injury, and progresivity of renal injury. Oxidative stress can be caused by the influx of free radicals into the human body through food that fried using reheated palm oil. Bilimbi fruit (Averrhoa bilimbi L.) contains antioxidants, such as flavonoid, saponin triterpenoid, vitamin A, and vitamin C that have the ability to neutralize free radicals. This research aimed to investigate the protective effect of bilimbi fruit extract on histological structure damage of renal cells induced by reheated palm oil and protective effect of increasing dose of bilimbi fruit extract. Methods: This was laboratory experimental research with post test only control group design. This research was done in Histology Laboratory of UNS Medical Faculty. Samples were Swiss webster mice, 2-3 months old and each weight Â± 20 g. Samples were 30 mice and obtained by incidental sampling. Samples divided randomly into five groups, each group consisted of six mice. The normal control group (KKn) was given distilled water only. The negative control group (KK(-)) was given reheated palm oil only with 0,2 ml/20 g BB dose. The first treatment group (KP1), the second treatment group (KP2), the third treatment group (KP3) were given bilimbi fruit extract with the dose of 5.6 mg/20 g weight, 11.2 mg/20 g weight, 22.4 mg/20 g weight respectively and induced by reheated palm oil with 0,2 ml/20 g BB dose for 14 days. At the 15th day, mice were sacrificed then right and left kidney were taken for preparation with HE staining. Renal cells damage were identified by counting the pyknosis, karyorrhexis, and karyolysis nucleus of proximal tubule cells from 50 renal cell mice. Data were analyzed with One-Way ANOVA and Post Hoc Multiple Comparisons-LSD (Î±=0.05). Results: There were differences in the number of damaged nucleus (pyknosis, karyorrhexis, and karyolysis) of proximal tubule epithelial cells between five groups and this difference was statistically significant (p=0.000). LSD test showed that there were significant differences between KKn-KK(-), KKn-KP1, KKn-KP2, KKn-KP3, KK(-)-KP1, KK(-)-KP2, KK(-)-KP3, KP1-KP2, KP1-KP3, and KP2-KP3 (p<0.05). Conclusions: Bilimbi fruit extract shows the protective effect to the histological structure damage of miceâs renal cells induced by reheated palm oil. The increasing of dose of the Bilimbi fruit extract improves the protective effect to miceâs renal cells. Keywords: Averrhoa bilimbi L., reheated palm oil, renal histological damageÂ